Caracterização estrutural e atividade anti-inflamatória em modelo de aterosclerose em camundongos de uma galactana sulfatada da alga vermelha Acanthophora muscoides - Quinderé, Ana Luíza Gomes (2015)
Sulfated galactans from red marine algae are polysaccharides with heterogeneous structures that have presented a variety of potentially therapeutic biological effects including anticoagulant, anti-thrombotic and anti-inflammatory, however, their potential activity as anti-inflammatory agent in the treatment of atherosclerosis, a chronic inflammatory disease that culminates with thromboembolic disorders, has not been previously studied. Furthermore, experimental data from animal models and clinical studies support connections between the hemostasis and inflammation in atherogenesis. These interfaces among inflammation and thrombogenesis have been suggested as targets for pharmacological intervention to reduce disease progression. Herein, we determined the chemical structure of a novel sulfated galactan obtained from the marine alga Acanthophora muscoides (fraction AmII) and analysed its effect on a mice model of atherosclerosis in 10-week aged apolipoprotein E deficient (ApoE−/−) mice under high-cholesterol diet for additional 4 or 11 weeks. Fraction AmII (10 mg/kg) or Vehicle were subcutaneously injected from week 2 until 4 of the diet or from week 6 until week 11 of the diet. In vitro assays of macrophage chemotaxis were also performed. The structure of the complex sulfated galactan was characterized by solution nuclear magnetic resonance and its molecular mass was determined by gel permeation chromatography and polyacrylamide gel electrophoresis. The sulfated galactan from A. muscoides presents a molecular mass of ~ 20kDa and an alternating 4-linked α-galactose and 3-linked β-galactose, substituted with sulfate esters and methyl ethers along with the occurrence of 3,6-anhydro-α-galactoses. In the 4 weeks diet model, treatment with fraction AmII did not alter the atherosclerotic plaque size, and other intraplaque features of vulnerability (such as lipid, neutrophil, macrophage, MMP-9 and collagen contents). In the 11 weeks diet model, treatment with fraction AmII reduced intraplaque macrophage and tissue factor (TF) content as compared to Vehicle-treated animals. Intraplaque TF co-localized and positively correlated with macrophage rich-areas. No changes on atherosclerotic plaque size, and other intraplaque features of vulnerability, such as lipid, neutrophil, MMP-9 and collagen contents, were observed. Moreover, mRNA expression of MMPs, chemokines and genetic markers of Th1/2/reg/17 lymphocyte polarization within mouse aortic arches and spleens was not affected by AmII treatment. In vitro, treatment with AmII dose-dependently reduced macrophage chemotaxis without affecting TF production. Overall, the chronic AmII treatment was well tolerated. In conclusion, our results indicate that AmII treatment reduced intraplaque macrophage content, by impacting on cell recruitment, and, concomitantly, intraplaque TF content of potential macrophage origin in atherosclerotic mice.